دورالنظام الضريبي بالأعتماد على المهن الحرة واثره على الموازنة التشغيلية (مستل) - أحمد, رزگار على; عمر, ناز غفور (Sulaimani Journal for Humanities, 2022)
The research objective to explain the evaluation of the tax system and its role in financing the general state budget, identifying the procedures of its tax system, and trying to benefit from that in evaluating the tax system and then the possibility of enhancing tax revenues in a way that reduces the risks of dependence on oil revenues, as well as identifying on tax systems and the evolution of the tax system as well as the development of the budget deficit and trying to find a relationship between them and the role of free professions in tax systems. We will learn in this research on how to activate the role of taxes in reducing the budget deficit. The research reached a number of conclusions, the most important of which are: The decrease in the average percentage of tax revenues' contribution to financing the general state budget.